(3OhQ GdbjGSGJ hGdENJHGQGJ GdaSjhdhLjI aj JfXje GdYedjI GdJOQjHjI hJMSjf COGA GdSHGMjf heOi EYJeGO GdeOQHjf YdjgG(B: (3OQGSI ebGQfI Hjf GdENJHGQGJ GdaSjhdhLjI GdeSHM hGSJWdGY CQGA GdeOQHjf ef eNJda LgGJ GdhWf s - (3eQSdj, eMeOs; (3Hf TQfjf, YHO GdMejOs; (3eYgO GdJQHjI GdHOfjI h GdQjGVjI, LGeYI GdLRGFQ (B3 s ((3GdLRGFQ s, 2018)
(3gOa GdOQGSI gh Gdhbha GdejOGfj Ydi CgejI GdbjGSGJ hGdGNJHGQGJ GdajSjhdhLjI aj JfXje YedjI GdJOQjH HeG JhaQg ef eDTQGJ gGeI Yf MGdI GdSHGMI ef GdfGMjI GdhXjajI, ceG SYJ GdOQGSI Gdi QUO fXQI hJaGYd GdeOQHjf eY gPg GdGNJHGQGJ heOi GYJeGOge YdjgG heG gj Cge GdeYhbGJ GdJj JMhd Ohf GMJdGdgG ddecGfI GdeWdhHI cCSGS Ydej WdH dHQeLI GdJOQjH MjK Je JMOjO YjfJjf GdGhdi JeKdJ aj GdSHGMjf GdPjf GLQjJ Ydjge GdGNJHGQGJ hGdKGfjI JeKdJ aj GdeOQHjf GdPjf QUOJ CQGFge ef GdLgGJ GdCQHY ddhWf s
(3GdOcJhQGgs
Keywords: (3GdENJHGQGJ GdaSjhdhLjIs; (3GdJOQH GdQjGVj GdfNHhjs; (3GdSHGMjfs